Entrepreneurial passion: A bibliometric study - Cazella, Carla Fabiana; Machado, Hilka Pelizza Vier (REGEPE Entrepreneurship and Small Business Journal, 2022)
Purpose: This study aims to identify the state of the art of publications on entrepreneurial passion, as well as the evolution and potential for future research. Design/methodology/approach: We conducted a bibliometric study on entrepreneurial passion in the Scopus, Web of Science and Science Direct databases. With the help of the Start software, we selected 665 scientific articles in the bibliometric analysis, and after the exclusion criteria, 64 articles remained in the sample. Main findings: The bibliometric analysis enabled us to describe the evolution of publications in the field, the most cited studies, the contribution of journals, and the main topics researched. The thematic analysis shows there is a field for future studies. Theoretical/methodological contributions: The study points, through the publications analyzed, the effects of entrepreneurial passion, both as a dependent variable, independent and mediator or moderator. With this, it presents a broad panorama that allows to evaluate the effects of passion on the behavior of entrepreneurs. As a practical contribution, knowledge about entrepreneurial passion can help graduate studies and researchers build research agendas. For entrepreneurs, the results point to the multiple effects of passion, which can encourage them to seek ways to develop it in their businesses. For educational institutions that work with entrepreneurship, the discussions presented here can help build entrepreneurship education programs and practices. Originality/value: The study points out an overview of publications on the theme entrepreneurial passion. Practical & Social implications: this study can assist graduate students and researchers in building research agendas. For entrepreneurs, the results point to the multiple effects of entrepreneurial passion, which can stimulate them to seek to develop it. For educational institutions that work with entrepreneurship, discussions can help build programs and entrepreneurial education practices. JEL Classification: L26, L31, G41